Bioactive glass (type 45S5) nanoparticles: in vitro reactivity on nanoscale and biocompatibility - Mackovic, Mirza; Hoppe, Alexander; Detsch, Rainer; Mohn, Dirk; Stark, W. J.; Spiecker, Erdmann; Boccaccini, Aldo R. (Journal of Nanoparticle Research, 2012)
Bioactive glasses represent important biomaterials being investigated for the repair and reconstruction of diseased bone tissues, as they exhibit outstanding bonding properties to human bone. In this study, bioactive glass (type 45S5) nanoparticles (nBG) with a mean particle size in the range of 20–60 nm, synthesised by flame spray synthesis, are investigated in relation to in vitro bioreactivity in simulated body fluid (SBF) and response to osteoblast cells. The structure and kinetics of hydroxyapatite formation in SBF were investigated using transmission electron microscopy (TEM), X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FT-IR) revealing a very rapid transformation (after 1 day) of nBG to nanocrystalline bone-like carbonated HAp. Additionally, calcite is formed after 1 day of SBF immersion because of the high surface reactivity of the nBG particles. In the initial state, nBG particles were found to exhibit chain-like porous agglomerates of amorphous nature which are transformed on immersion in SBF into compact agglomerates covered by hydroxyapatite with a reduced size of the primary nanoparticles. In vitro studies revealed high cytocompatibility of nBG with human osteoblast cells, indicated through high lactatedehydrogenase (LDH) and mitochondrial activity as well as alkaline phosphatase activity. Hence, this study contributes to the understanding of the structure and bioactivity of bioactive glass (type 45S5) nanoparticles, providing insights to the phenomena occurring at the nanoscale after immersion in SBF. The results are relevant in relation to the understanding of the nanoparticles’ bioreactivity required for applications in bone tissue engineering.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.bioact
Keywords: Nanoparticles; Bioactive glass; TEM; Hydroxyapatite; Osteoblast